2020
DOI: 10.18632/aging.202182
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutations are negatively correlated with immunity in colon cancer

Abstract: The heterogeneity of colon cancer tumors suggests that therapeutics targeting specific molecules may be effective in only a few patients. It is therefore necessary to explore gene mutations in colon cancer. In this study, we obtained colon cancer samples from The Cancer Genome Atlas, and the International Cancer Genome Consortium. We evaluated the landscape of somatic mutations in colon cancer and found that KRAS mutations, particularly rs121913529, were frequent and had prognostic value. Using ESTIMATE analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Moreover, some scholars have suggested that TTN and TP53 double mutations may take part in tumorigenesis by influencing downstream pathways through the participation of other co-expressed genes on the signaling network (39,40). Similarly, when KRAS is mutated, the downstream signaling pathway (mitogenactivated protein kinase, MAPK) is activated, leading to cell proliferation and tumor progression (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some scholars have suggested that TTN and TP53 double mutations may take part in tumorigenesis by influencing downstream pathways through the participation of other co-expressed genes on the signaling network (39,40). Similarly, when KRAS is mutated, the downstream signaling pathway (mitogenactivated protein kinase, MAPK) is activated, leading to cell proliferation and tumor progression (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the concept of tumor-promoting inflammation has been tightly associated with KRAS mutations [1]. In fact, in colorectal cancers, the majority of the cases with a high prevalence of KRAS mutations correlate with chronic inflammatory diseases [24]. KRAS and its downstream interactors are described as capable of shaping the immune microenvironment through the induction of the nuclear factor kappa light chain enhancer of activated B cells (NF)-kB signaling, which in turn promotes the transcription of several cytokines and chemokines, including interleukin (IL)-1α/β, IL-6, tumor necrosis factor α (TNF-α), Cys-X-Cys Chemokine (CXCL)-1, 2, 5, and 8, monocyte chemoattractant protein 1 (MCP-1 or CCL2), inducible nitric oxide synthase (iNOS), intracellular adhesion molecule 1 (ICAM-1), and endothelial leukocyte adhesion molecule 1 (ELAM1) [1,32].…”
Section: Kras and The Inflammatory Tumor Microenvironment Modulationmentioning
confidence: 99%
“…Colorectal cancer was, in 2020, the third most frequently diagnosed cancer and the second leading cause of cancer-related deaths in both sexes worldwide [15]. KRAS mutations are present in about 52% of colorectal cancer cases and are in the top 5 of mutated genes in 2 different databases, namely, the International Cancer Genome Consortium (ICGC) and The Cancer Genome Atlas (TCGA), along with APC, TP53, and TIN [1,[23][24][25][26]. Oncogene KRAS activating mutations KRAS G13D , KRAS G12D , and KRAS G12V are the most frequent mutations in colorectal cancer, with the codon 12 being the most affected [8,12,25,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations